The effect of a 12 week core training regimen on electromyographic activation in national-level junior swimmers - Hibbs, A. E.; Weston, M.; Thompson, K. G.; Spears, I. R.; Dixon, J. (Journal of Athletic Enhancement, 2014)
Knowledge of muscle activation during core training exercises over the duration of a training program would enhance our understanding of the physiological responses to training. The purpose of this study was to quantify the effect of a 12-week core training regimen on neuromuscular activation in swimmers. Ten national-level junior swimmers performed a core exercise regimen three times a week over a 12-week training period. Surface electromyographic (EMG) measurements from 6 core muscles were taken pre- (0 weeks), mid- (6 weeks) and post-training (12 weeks). Analysis was carried out on the EMG activity during maximal voluntary isometric contractions (MVCs) and on the normalized and non-normalized EMG values during the core exercises. MVC EMG activity increased with the intervention in all muscles. The magnitudes of changes in MVC EMG activity were greater during the initial phase (effect sizes - standardized mean differences 0.32 to 1.01) compared to the second phase (effect sizes -0.20 to 1.04). Substantial reductions were observed in the normalized EMG data, with these effects being greater during the initial phase (effect sizes -1.54 to -0.28) compared to the second phase (effects sizes -1.12 to -0.22). There were also substantial reductions in non-normalized absolute EMG activity in both the initial (effect sizes -2.73 to -0.27) and second (effects sizes -1.27 to -0.20) phases. Over the 12 week training program substantial neuromuscular adaptations occurred in the core muscles; activation during the core exercises reduced, whilst activation during the MVCs increased. These adaptations are indicative of improvements in neuromuscular strength and efficiency. Changes in EMG data provide objective measures of neuromuscular adaptation which can inform future iterations of training regimens for athletic populations.